The colony : faith and blood in a promised land - Denton, Sally (Liveright Publishing Corporation, 2022)
"A shocking massacre in 2019 sparks a probing investigation into the strange, violent history of a polygamist Mormon outpost in Mexico. A harmless, unassuming caravan of women and children was ambushed by masked gunmen in northern Mexico on November 4, 2019. In a massacre that produced international headlines, nine people were killed and five others gravely injured. The victims were members of the La Mora and LeBaron communities-fundamentalist Mormons whose forebears broke from the LDS Church and settled in Mexico when polygamy was outlawed. In The Colony, the best-selling investigative journalist Sally Denton picks up where initial reporting on the killings left off, and in the process tells the violent history of the LeBaron clan and their homestead, from the first polygamist emigration to Mexico in the 1880s to the LeBarons' internal blood feud in the 1970s to the family's recent alliance with the NXIVM sex cult. Drawing on sources within Colonia LeBaron itself, Denton creates a mesmerizing work of investigative journalism in the tradition of Under the Banner of Heaven and Going Clear"--